2011
DOI: 10.1590/s0100-69162011000600003
|View full text |Cite
|
Sign up to set email alerts
|

Regulated deficit irrigation and tommy atkins mango orchard productivity under microsprinkling in brazilian semi arid

Abstract: ABSTRACT:This study aimed to test controlled levels of water deficiency in soil in mango trees, under microsprinkling irrigation, in semi-arid conditions, and to evaluate its effect in the productivity and fruits quality. The deficits were applied in the phases I, II and III of growth of the fruit, during the productive cycles of the mango tree in 2006 and 2007. The experiment in both cases was arranged in an entirely random design with 10 treatments and 3 repetitions, in the year I, and with 8 treatments and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 15 publications
1
26
2
6
Order By: Relevance
“…The results of this study differ from those reported by COTRIM et al (2011),which no significant differences at 5% probability on 'Tommy Atkins' mango tree productivity submitted to regulated deficit irrigation between treatments with 100, 80, 60, 40 and 30% of ETc under micro sprinkler systems and drip. The authors explained the results by rise of the water level in the study area, which prevented the effect of different irrigation depths.…”
Section: Production and Efficiency Of Water Use Under Partial Rootzoncontrasting
confidence: 99%
“…The results of this study differ from those reported by COTRIM et al (2011),which no significant differences at 5% probability on 'Tommy Atkins' mango tree productivity submitted to regulated deficit irrigation between treatments with 100, 80, 60, 40 and 30% of ETc under micro sprinkler systems and drip. The authors explained the results by rise of the water level in the study area, which prevented the effect of different irrigation depths.…”
Section: Production and Efficiency Of Water Use Under Partial Rootzoncontrasting
confidence: 99%
“…The daily irrigation time used for each treatment was used according to COTRIM et al (2011), SANTOS et al (2014a, NEVES et al (2013) and SANTOS & MARTINEZ (2013), considering 0.90 as the application efficiency. These determinations were performed using IRRIMANGA software, computational tool to obtain evapotranspiration and calculation of irrigation time for mango crop management (SANTOS, 2012).…”
Section: Thementioning
confidence: 99%
“…Regulated deficit irrigation has been purposed in several crops, such as mango (Spreer et al, 2007;Silva et al, 2009;Cotrim et al, 2011Santos et al, 2014), pear (Marsal et al, 2008), grapevine (McCarthy, 2000;Ferreyra et al, 2002), peach (Gelly et al, 2004), loquat (Cuervas et al, 2007), melon (Fabeiro et al, 2002), olive (Iniesta et al, 2009), tomato (Savić et al, 2008), garlic (Cortés et al, 2003), onion (Olalla et al, 2004), beet (Fabeiro et al, 2003), bean and watermelon (González et al, 2009). These studies show water and energy saving, fruit quality improvement and yield increase.…”
Section: Introductionmentioning
confidence: 99%